Transcriptional Profiles Uncover Aspergillus flavus-Induced Resistance in Maize Kernels - Luo, Meng (MDPI, 2011)
Aflatoxin contamination caused by the opportunistic pathogen A. flavus is a major concern in maize production prior to harvest and through storage. Previous studies have highlighted the constitutive production of proteins involved in maize kernel resistance against A. flavus’ infection. However, little is known about induced resistance nor about defense gene expression and regulation in kernels. In this study, maize oligonucleotide arrays and a pair of closely-related maize lines varying in aflatoxin accumulation were used to reveal the gene expression network in imbibed mature kernels in response to A. flavus’ challenge. Inoculated kernels were incubated 72 h via the laboratory-based Kernel Screening Assay (KSA), which highlights kernel responses to fungal challenge. Gene expression profiling detected 6955 genes in resistant and 6565 genes in susceptible controls; 214 genes induced in resistant and 2159 genes induced in susceptible inoculated kernels. Defense related and regulation related genes were identified in both treatments. Comparisons between the resistant and susceptible lines indicate differences in the gene expression network which may enhance our understanding of the maize-A. flavus interaction.